2009
DOI: 10.1111/j.1750-3841.2009.01204.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Sensory and Food Quality: The R‐Index Analysis

Abstract: The accurate quantification of sensory difference/similarity between foods, as well as consumer acceptance/preference and concepts, is greatly needed to optimize and maintain food quality. The R-Index is one class of measures of the degree of difference/similarity, and was originally developed for sensory difference tests for food quality control, product development, and so on. The index is based on signal detection theory and is free of the response bias that can invalidate difference testing protocols, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 58 publications
0
36
0
3
Order By: Relevance
“…Sensory analytical data were collected using the Compusense  data capture system (Compusense Inc., Guelph, Canada). The R-index of each test sample relative to the control was estimated 10 and compared with the critical R-Index at P < 0.05 12 to determine if the samples were significantly different from the reference (0LC100E sample) at P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensory analytical data were collected using the Compusense  data capture system (Compusense Inc., Guelph, Canada). The R-index of each test sample relative to the control was estimated 10 and compared with the critical R-Index at P < 0.05 12 to determine if the samples were significantly different from the reference (0LC100E sample) at P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…10 This is an estimate of the probability that the breast meat produced from birds fed fish oil may be identified as being different from the reference (0LC100E) meat. The R-index ranges in value from 50% (where a judge cannot discriminate between the sample and reference meat, and so has to guess whether they are different, and therefore has a 50% chance of www.soci.org C Rymer, DI Givens being correct) and 100% (where a judge can discriminate perfectly between the two meats).…”
Section: Sensory Analysismentioning
confidence: 99%
“…In meat products, R-index values greater than 50% indicate a higher hedonic rating (Pasin et al 1989). Added pineapple fiber had no effect on sausage firmness (R-index = 50%), whereas the higher R-index value close to 100% (90.29%) indicated that samples formulated with cactus pear fiber were clearly preferred by judges (Lee and Van Hout 2009). For taste, R-index values were slightly higher for pineapple fiber samples than for cactus pear fiber (83.75 and 71.24%, respectively), with a slight preference for sausages containing pineapple fiber.…”
Section: R-indexmentioning
confidence: 91%
“…Bi (2005) specified the equivalence test problem and discussed several approaches. Applications of equivalence tests were proposed for different situations like analysis of the R-index (Bi, 2006;Lee & van Hout, 2009), d 0 as determined from forced-choice methods (Bi, 2011a), in the framework of Bayesian models for difference and preference tests including the evaluation of equivalence hypotheses Bi (2011b), and for unreplicated paired comparisons (Bi, 2007a). For replicated paired comparisons, Bi (2007b) proposes an approach based on the Beta-binomial model, using the overdispersion parameter as a nuisance parameter only without defining explicit margins for it and therefore unlike the approaches discussed in the previous section.…”
Section: Bibliographic Notesmentioning
confidence: 99%